2012
DOI: 10.1080/19338244.2011.573023
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Metallic Foreign Body Injuries Due To Suboptimal Ocular Protection

Abstract: Retrospective review of 100 consecutive presentations of metallic corneal foreign body to the Royal Victorian Eye and Ear Hospital emergency department was undertaken between November and December 2009. The majority of the patients (97%) were male with a mean age of 42 ± 13 years (range 19-73 years). The most common mode of injury was grinding (88%). Nearly half (45%) of patients were wearing "safety eye wear" at the time of injury. Combination of 25-gauge needle and burr was the commonest method employed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 7 publications
1
30
0
3
Order By: Relevance
“…Occupational injury by corneal FB comprises 35%58% of all ocular trauma (9,10) , and more frequently affects young men (11) . These preventable injuries cause additional bur den on the national economy, adjustment problems, and psycho logical morbidity (5,12) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Occupational injury by corneal FB comprises 35%58% of all ocular trauma (9,10) , and more frequently affects young men (11) . These preventable injuries cause additional bur den on the national economy, adjustment problems, and psycho logical morbidity (5,12) .…”
Section: Discussionmentioning
confidence: 99%
“…Despite wearing goggles, 43% patients sustained injuries. In a similar study, 45% patients sustained an eye injury while wearing some form of eye protection (11) . In this context, new designs should be implemented and workplace standards should be adjusted to increase the protecti ve capabilities of goggles (7) .…”
Section: İnjury Mechanism Percentagementioning
confidence: 99%
See 1 more Smart Citation
“…A study reported the frequency of CFBI among metal workers in Turkey as being 37% (8). Secondary infection may also develop due to CFBI, ranging from keratitis to endopthalmitis (9). Vision loss may develop because of scar development at the visual axis (5).…”
Section: Introductionmentioning
confidence: 99%
“…CFBI is an ophtalmological emergency, and the foreign body must be removed from the cornea with a 25-gauge needle in a non-traumatic fasion. Postoperative proliferative antibiotic treatment has also been administered (9).…”
Section: Introductionmentioning
confidence: 99%